The Impact of the Global Financial Crisis on Poverty in the Philippines - Alellie B. Sobrevinas; Jeremy de Jesus; Celia M. Reyes (Philippine Institute for Development Studies (PIDS), 2010)
The recent global financial and economic crisis which started in the United States and expanded to other developed countries has, to some extent, affected developing countries as well. Given the vulnerability of most developing countries, it is important to monitor the impact of this global crisis on poverty. This study, therefore, aims to assess the impact of the crisis on poverty in the Philippines. The result of this study would serve as inputs to policymakers in prioritizing mitigating measures that would address the impact of the crisis. In this study, monitoring is done primarily through the conduct of CBMS surveys in selected sentinel sites. Household- and community-level data were collected to capture the different dimensions of poverty. In addition to the CBMS core indicators, specific indicators (including the outcome and impact indicators) were monitored to determine the impact of the global crisis. These indicators were identified based on the relevant key transmission channels for the Philippines including overseas employment and remittances, and local employment. The study also looked at the different coping mechanisms adopted by the households in response to the crisis. The study also attempted to identify who are able to access the programs which were being implemented in the community. Ten barangays all over the Philippines were selected to serve as poverty observatories or sentinel sites for monitoring the impact of the global crisis. Selection of these sites was also based on the relevant transmission channels for the Philippines. Results reveal that although the impact of the crisis is generally minimal, the crisis has affected some specific sectors in the economy. The degree of impact also varies among different groups of households. Hence, policies should be designed to mitigate the impact of the crisis on these affected sectors and groups of households.
Keywords: 330; community-based monitoring system; Philippines; global financial and economic crisis; impact transmission channels; CBMS indicators; household-coping strategies; program targeting; leakages and exclusion; poverty impacts; Finanzkrise; Armut; Soziale Lage; Privater Haushalt; Philippinen